Synthesis, characterization and antimicrobial screening of some novel furan-azetidinone hybrid compounds - JUDY JAYS; S MOHAN; J SARAVANAN (International Journal of Pharma and Bio Sciences, 2018)
A series of furan-azetidinone hybrid compounds were synthesized with the objective of arriving at potential lead antimicrobial compounds. The synthesis of 2-phenylcyano-N-phenylacetamide (1) was carried out by the condensation of ethyl cyanoacetate and aniline. This was the precursor for the synthesis of 2-amino-N, 4, 5-triphenyl furan-3-carboxamide (2). A series of Schiff bases 3 (a-h), were synthesized from 2-amino-N, 4, 5-triphenyl furan-3-carboxamide (2) by refluxing with various substituted aromatic aldehydes in ethanol using concentrated sulphuric acid as the catalyst. These were cyclized to give the furan-azetidinone hybrids 4 (a-h). Structures of the novel compounds were characterized by infrared (IR), 1H nuclear magnetic resonance (NMR) and mass spectral analysis. The title compounds were screened for their antibacterial and antifungal activity by the cup plate method. All the compounds exhibited moderate activity against the screened microorganisms compared with the standard drugs. Compound 4b was found to be the most active against the screened bacterial and fungal strains.